Climate risk management strategies and household food and nutrition security of rice farmers : evidence from rural Thailand - Nath, Toma Deb; Datta, Avishek; Zulfiqar, Farhad; Seksan Papong; Tsusaka, Takuji W.; Himanshu, Sushil Kumar; His Majesty the King{u2019}s Scholarship (Thailand) (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
Climate change (CC) is expected to alter environmental conditions for crop growth and require adjustments in crop management practices, amplifying both the frequency and extent of farmers{u2019} adaptation practices. Climate change poses profound challenges and uncertainties for rice farmers, threatening their livelihoods and the stability of rice production. This has heightened concerns over household food and nutrition security, as rice serves as the primary food source for more than 50% of the world{u2019}s population and contributes over 20% of global calorie consumption. This reliance compels farmers to adopt climate risk management (CRM) strategies to alleviate climate-related vulnerabilities. However, it is a challenge to accurately perceive the required adaptations against extreme climate events and eventually adopt the most appropriate measures. This research assessed the impact of adoption of CRM strategies on rice farmers{u2019} food and nutrition security. The first part of the research assessed the consistency of rice farmers{u2019} CC perceptions with long-term meteorological trends and examined the intensity of their adoption of CRM strategies. This study was conducted in the climatically-vulnerable northeast region of Thailand. Primary data were collected from 402 rice farmers. Secondary climate data on temperature and rainfall were collected for 32 years (1991{u2013}2022). Farmers perceived a rising temperature trend and a changing rainfall pattern characterized by fewer rainy days with higher rainfall intensity, which is consistent with the long-term meteorological trend. A majority of farmers (48.9%) had medium adoption of CRM strategies (total score: 16{u2013}30). The top four adopted CRM strategies were adopting other income-generating activities, direct seeding, changing planting dates and time, and solar irrigation. Farmers{u2019} adoption decision was influenced by education, farming experience, training experience, rice cultivated area, and credit access. Furthermore, education, household size, farming experience, access to information sources, training experience, annual net family income, credit access, soil fertility, and distance from the market played significant roles in farmers{u2019} intensity of adoption. This study recommends policy interventions to increase the rate of adoption by disseminating information of CC adaptation strategies and providing on-farm demonstration training to the farmers by considering local people{u2019}s knowledge and resource base.The second part of the research investigated the impact of CRM strategies on the income of rice farmers in Thailand. The data were collected through a survey with randomly selected 402 rice farmers in six districts of Chaiyaphum province using a pre tested structured questionnaire. The data analysis employed the propensity score matching technique to assess the effect of CRM strategies on farmers{u2019} income. The analysis revealed that CC was perceived as adversely affecting crop production, leading them to adopt various CRM strategies to mitigate these effects. Education, farming experience, training experience, rice cultivated area, and less access to credit were found to be pivotal factors influencing the adoption of CRM strategies. Importantly, the adoption of CRM strategies exhibited positive average effects on the adopters{u2019} incomes with the effect size being THB 37,000 (USD 1,057) per farm per annum. Consequently, this study advocates policymakers to focus on the identified determinants of the adoption of CRM strategies, which has the potential to ultimately boost farmers{u2019} income and overall livelihoods in climate-vulnerable areas. The third part of the research examined the impact of the adoption of CRM strategies on rice farmers{u2019} food and nutrition security. Data were collected through the administration of a pre-tested questionnaire survey from the household heads by utilizing a multistage sampling technique; 402 rice farmers were sampled and interviewed in six districts of Chaiyaphum province, Thailand. The propensity score matching technique was employed to examine the adoption impact of CRM strategies on rice farmers{u2019} food and nutrition security. Food consumption score (FCS), dietary diversity score (DDS), and calorie intake score (CIS) were used as indicators of food and nutrition security. Six factors, including education, farming experience, training experience, rice cultivated area, credit access, and access to irrigation water, significantly influenced the adoption of CRM strategies. Moreover, rice farmers who adopted CRM strategies for managing climate-related risks had noticeably higher FCS, DDS, and CIS. Additionally, the adopters faced several problems in implementation and the non-adopters faced several barriers to the adoption of such strategies. This study suggests that policymakers should concentrate on the influential factors and address the barriers on a priority basis that drive the adoption of CRM strategies, which can ultimately lead to a boost in farmers{u2019} food and nutrition security status through effective policy interventions.
A Dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Agricultural Systems and Engineering
Thesis (Ph.D.) - Asian Institute of Technology, 2025
Keywords: Rice farmers -- Risk assessment -- Thailand; Climatic changes -- Risk management -- Thailand; Food security -- Thailand